Energy Price Impact on BRIC Stock Markets: A Granger Causality Analysis - Pessoa, Gustavo; Ponkratov, Vadim; Philippov, David; Shvyreva, Olga; Kuznetsov, Nikolay; Elyakova, Izabella; Mikhina, Elena; Kotova, Natalya; Pozdnyaev, Andrey; Durmanov, Akmal; Bloshenko, Tatiana (Ital Publication, 2024)
Energy prices and the stock market are two of the crucial factors in the evolving landscape of global finance, particularly in major emerging economies. However, research on how energy price changes impact stock markets in BRIC countries remains limited, despite their diverse roles in global energy markets and economies. This study investigates the causal dynamics between energy prices and stock market performance in BRIC countries, aiming to uncover short-term fluctuations and long-run relationships in these major emerging economies. Utilizing daily data from 2013 to 2023, stationarity tests, cointegration analysis, and Granger causality tests are employed to examine these relationships. Key findings reveal weak evidence of a long-run equilibrium between energy prices and stock market indices, challenging previous assumptions about their cointegration. More significantly, the findings uncovered a strong unidirectional Granger causality from oil prices to all BRIC stock market indices, while gas prices show a more selective influence. Notably, no evidence of reverse causality from stock markets to energy prices was found, highlighting the exogenous nature of global energy prices in relation to BRIC stock markets. This study uniquely analyzes oil and gas price effects on BRIC stock markets, offering insights for investors and policymakers amid increasing commodity-financial market integration. Doi: 10.28991/ESJ-2024-08-06-015 Full Text: PDF